EKSPLORASI KREATIVITAS SISWA KELAS RENDAH MELALUI KEGIATAN ART AND CRAFT PADA SEKOLAH BERBASIS MONTESSORI - Maharani, Anggita; Nugrahanta, Gregorius (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The dominance of teacher-centered learning leaves elementary school students with little room to express their creativity freely. This study aims to describe the development of lower-grade students' creativity through art and craft activities within the Practical Life framework of the Montessori approach. A qualitative descriptive approach was used, involving 19 students in grades 1–3 and two classroom teachers at a Montessori-based elementary school in Yogyakarta. Data were collected through participant observation and in-depth interviews, then analyzed through data reduction, data presentation, and conclusion drawing. All six creativity indicators, fluency, flexibility, originality, elaboration, independence, and self-confidence, were observed to emerge during the activities. Fluency, elaboration, and self-confidence developed most prominently. Flexibility, originality, and independence emerged but unevenly, these three indicators still require more consistent stimulation. Art and craft activities within the Montessori Practical Life framework proved effective as a meaningful learning vehicle for lower-grade students' creativity.